Plurilingualism and polish teenage learners of english - Otwinowska-Kasztelanic, Agnieszka (Linguarum Arena, 2018)
Using several languages has become a norm for those who want to learn and work in the European Union. However, teaching for plurilingualism is also a challenge. The present paper first clarifies the notions of plurilingualism and multilingualism, then discusses the role of crosslinguistic similarity in language learning in the case of European languages. It also shows how lexical crosslinguistic similarity can be used in teaching typologically related and unrelated languages, and discusses the key factors in noticing such similarity. The research presented reports on examining and raising language awareness of Polish‑English cognate vocabulary in the case of a group of Polish teenage learners of English. It presents the results of a small‑scale study in quasi‑experimental design, as well as qualitative research on the learners’ opinions and attitudes. Finally, the paper presents implications for language pedagogy and focuses on the fact that awareness raising may affect the learners’ plurilingual competence.